2016
DOI: 10.15369/sujms.28.123
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cell Migration and Invasion, and Their Association with Periostin in Anaplastic Thyroid Cancer, Using a Real-time Cell Analyzer

Abstract: : Anaplastic thyroid cancer ATC is known to be a highly malignant cancer of the thyroid with a high mortality rate. In a previous study, we used realtime cell analysis RTCA to analyze cell migration and invasion of oral squamous cell carcinomas OSCCs of the tongue and oor of the mouth. In the present study, we investigated cell migration and invasion of ATC using RTCA, as well as their association with periostin, matrix metalloproteinases MMPs , and integrins. Experiments were performed on TCO-1 and HTC / C3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In particular, EGCG inhibited TCO-1 cell adhesion and proliferation. The ndings of the present study show that at 10 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In particular, EGCG inhibited TCO-1 cell adhesion and proliferation. The ndings of the present study show that at 10 .…”
Section: Discussionsupporting
confidence: 61%
“…In a previous study using RTCA we showed that EGCG inhibited cell migration and invasion in oral squamous cell carcinomas OSCCs 9 . Moreover, we have demonstrated that anaplastic thyroid cancer ATC cells TCO-1 have high migratory and invasive activity in association with high periostin expression 10 . In particular, TCO-1 cells exhibit very high periostin expression compared with other cell lines tested 10 .…”
mentioning
confidence: 88%